Certain uncertainty : leading with agility and resilience in an unpredictable world - Dearlove, Des (John Wiley & Sons, Inc., 2023)
"In the last 25 years we have seen a series of major disruptions to business as usual. There was the Asian financial crisis in 1997, the dotcom bust in 2000, the SARs crisis in 2002, the tsunamis in 2004 and 2011, the global financial crisis in 2008, the Arab Spring of 2011, the Ebola outbreak in 2014 and covid-19 in 2020. All of these were unexpected events that have huge impact. Add in the threat of global warming, oil price volatility and a refugee crisis around the world, a war in Ukraine, plus the ever-present threat of another pandemic, and the disruptions are incessant. Whether we like it or not, we have to accept that the era of phony certainty is over. What has replaced it is a growing awareness that we cannot hope to control events but must learn to be better at responding to them. We need to build resilience and agility into our lives, including the way business operates. Change is now a constant, disruption is to be expected, and requires an adaptable response. The hope is that this collection of advice and fresh thinking from accomplished business leaders around the world will help the leaders of tomorrow on their journey"--